CONSEQUENCES OF BIOTECHNOGENIC AND COEVOLUTIVE DEVELOPMENT IN THE PROCESS OF BIOTECHNOLOGICAL EVOLUTION (in a socio-philosophical perspective) - Shermanov Isobek Chilmamatovich; Jumanov Hasan Nasritdin o’g’li (World Scientific Research Journal, 2025)
Annotation: This article analyzes the socio-philosophical consequences of biotechnological evolution, biotechnogenic and coevolutionary development. The historical formation of biotechnology, genetic engineering, artificial biosystems, and synthetic biology are examined. Particular attention is paid to the economic, environmental, and social aspects of biotechnology, as well as its current and future prospects.